Audit Keamanan Jaringan Komputer Server dari Serangan DDoS Menggunakan Snort Intrusion Detection System - Yuhandri Yunus; Syafri Arlis; M.Iqbal, M.Iqbal (AI Society & STMIK Indonesia, 2024)
Network security is a crucial aspect for educational institutions that rely on information technology for operational activities, including teaching and learning processes. SMKS YPPI Tualang, a private school in Riau that is part of PT Indah Kiat Pulp and Paper Tbk's CSR program, faces serious threats from Distributed Denial of Service (DDoS) attacks, which can cause significant disruptions to network services. DDoS attacks involve multiple computer systems overwhelming a server with excessive traffic, leading to service disruptions. This study aims to enhance network security at SMKS YPPI Tualang through a comprehensive security audit and the implementation of Snort, an Intrusion Detection System (IDS) effective in detecting and preventing DDoS attacks. By analyzing potential security gaps and vulnerabilities, this study is expected to contribute to mitigating the risk of DDoS attacks, thereby ensuring the continuity of the school's operations. The results of this study indicate that the implementation of Snort can improve early threat detection and strengthen the school's network security.